(untitled) (Acta Scientiarum. Language and Culture, 2011)
Current essay analyzes the materialization of media discursive practices which give identity to the journalist as a subject. The discursive event of such production is investigated within the context of the voting held at the Brazilian Federal Court of Justice on the 17th June 2009 which ruled on the non-obligatory of a journalist university diploma to warrant the profession. Since it is an event beyond the casual range, it enhances the rise and transformation of knowledge in society and in new forms of power. Enunciation sequences in six articles published by the magazines Veja and IstoÉ and by the newspapers Folha de S. Paulo on-line and O Estado de São Paulo are analyzed. Foregrounded on the French Discourse Analysis (DA), especially on Michel Foucault’s theoretical presuppositions, the journalists’ identity is built on notions of the freedom of speech and of the press. Further, in the enunciations, the ‘ability myth’, as an innate and/or acquired factor received through experience in the exercise of the profession, also produces effects on identity.